Patau Syndrome With Holoprosencephaly: A Multidisciplinary Interactive Case-Based Learning Exercise - Edward Klatt; Tina Thompson (Association of American Medical Colleges, 2010)
Abstract This educational resource is organized as a case history with laboratory and ultrasound findings for discussion by a group of students. It is woven around a pregnancy with abnormal findings that are the result of Patau syndrome. Several fetal central nervous system (CNS) malformations are explored from a basic science, diagnostic, and counseling standpoint. This case study is designed to support basic science education in genetics and pathology disciplines and to integrate the use of diagnostic tools and testing in prenatal care to facilitate understanding of the application of basic science knowledge to patient care and counseling. This case study could be discussed in a minimum of 15 minutes if much of the information in the facilitator guide were given to the students for self-study. Most of the key concepts could be discussed within an hour. Facilitators can be directed to promote student discussion by asking the students to explain the findings and to compare and contrast CNS malformations and their causes. Educational goals include an understanding of genetic mechanisms, embryologic development, prenatal laboratory testing, and parental counseling regarding outcomes and options. The primary author field-tested a version of this exercise for 7 years (2002-2008) as part of a case-based learning module in genetic diseases, presented within a course teaching fundamentals of pathology in the second-year curriculum at the Florida State University School of Medicine. Suggestions for improvement by students and faculty have been incorporated to enhance its quality. Course evaluations by students in that venue pertinent to this group exercise ranged from 4.23 to 4.82 on a scale of 0 (worst) to 5 (best). Examination and quiz items scored in the 80% to 90% range.